2005
DOI: 10.1086/430692
|View full text |Cite
|
Sign up to set email alerts
|

AChandraX‐Ray Investigation of the Violent Interstellar Medium: From Dwarf Starbursts to Ultraluminous Infrared Galaxies

Abstract: We have analyzed observations with the Chandra X-Ray Observatory of the diffuse emission by hot gas in seven dwarf starburst galaxies, six edge-on starburst galaxies, and nine ultraluminous infrared galaxies. These systems cover ranges of $10 4 in X-ray luminosity, and several thousand in star formation rate and K-band luminosity (a proxy for stellar mass). Despite this range in fundamental parameters, we find that the properties of the diffuse X-ray emission are very similar in all three classes of starburst … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

33
173
2

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 103 publications
(208 citation statements)
references
References 53 publications
33
173
2
Order By: Relevance
“…However, these values are relatively high when compared to the study by Strickland et al (2004), who obtained kT = 0.11 keV and kT = 0.37 keV for a two-temperature model fitted simultaneously to eight starbursts whose X-ray point-sources had been removed. Also, Grimes et al (2005) only found two sources with kT > 0.5 keV among seven dwarf starbursts. The kT value we propose for Haro 2 agrees better with the values found by Grimes et al (2005) for their sample of ULIRGs.…”
Section: ) Obtaining Best Fits When O and Mg Abundances Were Z(omentioning
confidence: 91%
See 1 more Smart Citation
“…However, these values are relatively high when compared to the study by Strickland et al (2004), who obtained kT = 0.11 keV and kT = 0.37 keV for a two-temperature model fitted simultaneously to eight starbursts whose X-ray point-sources had been removed. Also, Grimes et al (2005) only found two sources with kT > 0.5 keV among seven dwarf starbursts. The kT value we propose for Haro 2 agrees better with the values found by Grimes et al (2005) for their sample of ULIRGs.…”
Section: ) Obtaining Best Fits When O and Mg Abundances Were Z(omentioning
confidence: 91%
“…Also, Grimes et al (2005) only found two sources with kT > 0.5 keV among seven dwarf starbursts. The kT value we propose for Haro 2 agrees better with the values found by Grimes et al (2005) for their sample of ULIRGs. As previously said, hard emission in Haro 2 is dominated by the point-like source X1.…”
Section: ) Obtaining Best Fits When O and Mg Abundances Were Z(omentioning
confidence: 91%
“…Indeed, the center of NGC 3628 resembles that of NGC 660 also by its complement of compact radio continuum sources (none coinciding with the nucleus) representing active regions in the circumnuclear star-burst contributing about 10% to the total radio continuum emission (Carral et al 1990), and by its H92α radio recombination line emission from high-density HII regions (n HII ≈ 10 4 cm −3 -Anantharamaiah et al 1993;Zhao et al 1997). The central core of NGC 3628 is also bright in X-rays, and the galaxy has an extended halo of soft X-ray emission surrounding a central outflow, apparently a galactic (star-burstdriven) super-wind bubble (Dahlem et al 1996(Dahlem et al , 1998Strickland et al 2004a,b;Grimes et al 2005;Flohic et al 2006). NGC 3628 may (Roberts et al 2001;González-Martín et al 2006) or may not (Dudik et al 2005) contain a low-luminosity AGN.…”
Section: Ngc 3628mentioning
confidence: 99%
“…Outflows are commonly observed in local U/LIRGs Rupke & Veilleux 2005;Rupke et al 2005a,b,c;Martin 2006;Sturm et al 2011;Rupke & Veilleux 2013;Veilleux et al 2013;Teng et al 2013;Spoon et al 2013;Rodríguez Zaurín et al 2013;Arribas et al 2014;Cicone et al 2014), and are likely a common cause of shocks. Several studies of shocks in nearby galaxies have linked them to superwinds produced by stellar feedback (Heckman et al 1990;Grimes et al 2005;Rich et al 2011;Hopkins et al 2012;Hong et al 2013) and AGN-driven outflows (Mazzarella et al 2012). Although these systems are relatively rare in the local universe, Le Floc'h et al (2005) have shown that high infrared luminosities may have been the norm at redshifts beyond 0.7.…”
Section: Introductionmentioning
confidence: 99%